SENAM ASMA DALAM UPAYA PENINGKATAN FUNGSI PARU PENDERITA ASMA DENGAN PENDEKATAN KEPERAWATAN KELUARGA DI RT 02 RW 05 KELURAHAN METESEH KOTA SEMARANG - Siwi, Adelia Rida Dara; Hani, Umi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Introduction: Asthma is a diseasenon-infectious characterized by shortness of breath andrecurrent wheezing. Affected individuals canexperience symptoms several times a day or a week.During an asthma attack, the lining of the bronchial tubesswell and can cause airwaysnarrows and reduces air inflow andout of the lungs. Purpose: Give an overviewapplication of fact-based practices in carefamily nursing with innovative asthma exercise forimprove lung function in asthmatics. Results :The results of the evaluation of asthma exercise found thatIncreased participation in health programscommunity from scale 2 to scale 4. Decreasedisease prevalence from a scale of 3 to a scale of 5strengthen the respiratory muscles that can createbreathing muscles work better. Familycpk I by preventing asthma recurrence fromincrease efforts to maintain family health.Conclusion: Results After the innovation program was carried outasthma exercise therapy in family nursing carecan provide an overview of the application in carefamily nursing with innovative asthma exercise forimprove lung function in asthmatics.